Production of inclusive ϒ(1S) and ϒ(2S) in p–Pb collisions at √sNN=5.02 TeV - Abelev, B.; Adam, J.; Adamovã, D.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agostinelli, A.; Agrawal, N.; Ahammed, Z.; Ahmad, N.; Ahmed, I.; Ahn, S.U.; et al. (Elsevier, 2015)
We report on the production of inclusive Υ (1S) and Υ (2S) in p–Pb collisions at √sNN = 5.02 TeV at the LHC. The measurement is performed with the ALICE detector at backward (−4.46 < ycms < −2.96) and forward (2.03 < ycms < 3.53) rapidity down to zero transverse momentum. The production cross sections of the Υ (1S) and Υ (2S) are presented, as well as the nuclear modification factor and the ratio of the forward to backward yields of Υ (1S). A suppression of the inclusive Υ (1S) yield in p–Pb collisions with respect to the yield from pp collisions scaled by the number of binary nucleon–nucleon collisions is observed at forward rapidity but not at backward rapidity. The results are compared to theoretical model calculations including nuclear shadowing or partonic energy loss effects.
Keywords: Quarkonia; Quark–gluon plasma; https://purl.org/pe-repo/ocde/ford#1.03.04